Exploring structural, functional, evolutionary, and genetic characteristics of sugar transporters in maize and their roles in abiotic stress tolerance - Md. Sohel Mia; Md Suzauddula; Tao Yang; Rui Li; Fang Li; Jianbo Mi; Chao Xia; Tanveer A. Wani; Seema Zargar; M. Atikur Rahman; Md. Mahmudul Hasan (PLoS ONE, 2026)
Sugars are the structural building blocks of carbohydrates, which are transported through a series of transporters in plant. To explore the molecular mechanisms of how transporters, play roles in uptake, transport and mobilization of sugars in maize, a series of bioinformatics analyses were done to identify and characterize the transporters. Following the analyses, 60 sugar transporters were identified in maize, which shared eight (STP, PLT, ERD6, INT, TMT, pGlcT, SUC, and VGT) clades during phylogenetic analysis. Due to having significant differences in molecular weight, multiple beta-strands, transmembrane helices, and 11–12 transmembrane domains, the transports might play significant variations in functional properties. Since most transporters are plasma membrane bound, and have the highest homolog pairs (39) with S. bicolor during synteny analysis, the transporters might be involved in intercellular sugar transport that are conserved and significantly duplicated during the process of evolution. The lowest binding affinity (ΔG: − 7.1 kcal/mol) in ZmVGT1-Suc docked complex, and most commonly found hydrogen bond mediated attachment of valine residue ligand might represent the complex stability and functional integrity of the complex. Indeed, the RMSD deviation of 1 (for ZmST10-Gal) to 3 Å (for ZmST10-Glu) among the docked complexes might guide the subtle conformational differences that could impact the functional roles of the complexes. Next, during co-expression analysis, clustering of 491 genes with 43 maize sugar transporter into four co-expression clusters and five different metabolic pathways might guide their inter regulatory roles in interacting different metabolic pathways. More specifically, co-expression of ZmSTP9 and ZmPLT10 with the MYB8 and A6b stress-responsive transcription factors might guide their stress regulatory mechanisms. The RNA-Seq based observation of differential tissue specific expression and expression under salinity, drought, nitrogen deficiency, and heat stress and qRT-PCR mediated validation of differential tissue specific expression and upregulation of ZmPLT1 , ZmPLT8 , ZmSTP1 , ZmTMT1 , and ZmSUC3 under salinity stress might guide their potential roles in abiotic stress tolerance. The plasma membrane localized validation of subcellular localization of ZmPLT1 and ZmPLT8 proteins might guide the consistent results between dry and wet lab experiments. Therefore, the identified and characterized maize sugar transporters through integrated dry and wet lab experiments might guide the future research in developing abiotic stress tolerant maize and exploring the molecular mechanism of stress tolerance trough transporter guided regulation of maize abiotic stress signaling pathways following circuit enabled synthetic biology approaches.